Patient Safety in Medical Education: Students’ Perceptions, Knowledge and Attitudes - Nabilou, Bahram (PLoS One, 2015)
Patient safety is a new and challenging discipline in the Iranian health care industry. Among the challenges for patient safety improvement, education of medical and paramedical students is intimidating. The present study was designed to assess students’ perceptions of patient safety, and their knowledge and attitudes to patient safety education. This cross-sectional analytical study was conducted in 2012 at Urmia University of Medical Sciences, West Azerbaijan province, Iran. 134 students studying medicine, nursing, and midwifery were recruited through census for the study. A questionnaire was used for collecting data, which were then analyzed through SPSS statistical software (version 16.0), using Chi-square test, Spearman correlation coefficient, F and LSD tests. A total of 121 questionnaires were completed, and 50% of the students demonstrated good knowledge about patient safety. The relationships between students’ attitudes to patient safety and years of study, sex and course were significant (0.003, 0.001 and 0.017, respectively). F and LSD tests indicated that regarding the difference between the mean scores of perceptions of patient safety and attitudes to patient safety education, there was a significant difference among medical and nursing/midwifery students. Little knowledge of students regarding patient safety indicates the inefficiency of informal education to fill the gap; therefore, it is recommended to consider patient safety in the curriculums of all medical and paramedical sciences and formulate better policies for patient safety.